Comparative effectiveness of different interventions on adherence to exercise-based CR among patients after percutaneous coronary intervention: a network meta-analysis of randomized controlled trials - Chengyu Xia; Yingjun Zheng; Liuxia Ji; Hui Liu (BMC Nursing)
Abstract Background Exercise-based phase II cardiac rehabilitation is critical for post-PCI patients, but adherence to exercise-based phase II cardiac rehabilitation remains low. Many studies aimed at improving adherence have been conducted in recent years, but the most effective interventions remain unclear. Hence, the objective of this study was to evaluate the effectiveness and ranks of various interventions in enhancing adherence to exercise-based phase II cardiac rehabilitation for post-PCI patients. Methods A network meta-analysis employing random effects was utilized to evaluate the effectiveness of different interventions. Bias evaluation was performed via the revised Cochrane risk of bias tool, with data analysis performed using STATA v15.0. The surface under the cumulative ranking was used to estimate the rankings among different interventions. Results In the final analysis, 30 RCTs with 4267 patients across 17 different interventions were included. The results showed that patients who received home-based cardiac rehabilitation combined with mobile health intervention had the best adherence to exercise-based phase II cardiac rehabilitation (83.8%), followed by hospital-based cardiac rehabilitation combined with mobile health intervention (79.9%). Conclusions This network meta-analysis identified home-based CR + mobile health intervention and hospital-based CR + mobile health intervention as the top two ranked interventions for improving adherence to exercise-based phase II CR in post-PCI patients. Healthcare providers may consider prioritizing the use of home-based cardiac rehabilitation combined with mobile health intervention in clinical practice, but still need to evaluate factors such as patient preference and Medicare reimbursement availability to develop customized interventions that are not only safe and effective but also satisfying to the patient.